2018
DOI: 10.1590/1678-4499.2017076
|View full text |Cite
|
Sign up to set email alerts
|

Statistical methods to study adaptability and stability in breeding lines of food-type soybeans

Abstract: The grains of food-type soybean cultivars, which are characterized by the absence of lipoxygenases and the presence of high levels of proteins and isoflavones, are regarded as functional foods with high acceptance by consumers. However, few cultivars of food-type soybeans are currently available in the Brazilian market. The aim of this work was to study the adaptability and stability of various genotypes of food-type soybeans and to compare the performance of methods, which are based on analysis of variance, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
1
23
0
1
Order By: Relevance
“…These results indicating the presence of variability among these components justify the use of stability statistics for the identification of stable genotypes with superior seed yield of soybean under the various environments. Maia et al [17], Yokomizo et al [18] and Freiria et al [19] analyzed the adaptability and stability of soybean genotypes and found that the mean squares of G, E and GEI were significant (p ≤ 0.01). Therefore, the environments evaluated were distinct and the soybean genotypes presented a differentiated performance in response to environmental variations.…”
Section: Ammi Anovamentioning
confidence: 99%
“…These results indicating the presence of variability among these components justify the use of stability statistics for the identification of stable genotypes with superior seed yield of soybean under the various environments. Maia et al [17], Yokomizo et al [18] and Freiria et al [19] analyzed the adaptability and stability of soybean genotypes and found that the mean squares of G, E and GEI were significant (p ≤ 0.01). Therefore, the environments evaluated were distinct and the soybean genotypes presented a differentiated performance in response to environmental variations.…”
Section: Ammi Anovamentioning
confidence: 99%
“…Users who research the associations between stability indexes (e.g., Woyann et al, 2018; Bornhofen et al, 2017; Freiria et al, 2018; Shahbazi, 2019) often find difficulties in computing the set of statistics and binding them into a “ ready-to-read ” file. provides an efficient solution for doing that.…”
Section: The Packagementioning
confidence: 99%
“…Although useful, these packages do not offer options to perform a complete analysis of MET data, i.e., to provide tools for all steps of the analysis (check, manipulation, analysis, and visualization of data). For example, requires as input data a two-way table containing genotype by environment means with genotypes in rows and environments in columns, but doesn’t provide any function to create quickly such table from data that often is in a “ long ” format in R. In addition, several studies often compare different stability methods (e.g., Woyann et al, 2018; Scapim et al, 2010; Bornhofen et al, 2017; Freiria et al, 2018; Shahbazi, 2019; Teodoro et al, 2019). This requires a range of different packages to be used, making it the coding tedious and difficult to follow.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is recommended that the regression models and other methods be used simultaneously to complement each other in estimating adaptability and phenotypic stability effects (Ferreira et al, 2006;Toler & Burrows, 1998). The use of these techniques is widespread in studies on plant species and many other commercial crops (Borges et al, 2010;Breseghello et al, 2011;Carbonell et al, 2007;Freiria et al, 2018). In microbiological studies, almost no reports have this focus (Gunnabo et al, 2019).…”
Section: Core Ideasmentioning
confidence: 99%